2014
DOI: 10.1002/jnr.23275
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure to ethanol of male mice before mating produces attention deficit hyperactivity disorder‐like phenotype along with epigenetic dysregulation of dopamine transporter expression in mouse offspring

Abstract: Preconception exposure to EtOH through the paternal route may affect neurobehavioral and developmental features of offspring. This study investigates the effects of paternal exposure to EtOH before conception on the hyperactivity, inattention, and impulsivity behavior of male offspring in mice. Sire mice were treated with EtOH in a concentration range approximating human binge drinking (0-4 g/kg/day EtOH) for 7 weeks and mated with untreated females mice to produce offspring. EtOH exposure to sire mice induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
76
2
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 67 publications
12
76
2
1
Order By: Relevance
“…The deficiencies in the markers of neurodevelopment and neurosteroid-sensitive receptors were associated with increased activity in the open field and environment exploration tests, with the preterm males more active than the control term males. Similar results are seen in mice expressing an attention deficit hyperactivity disorder-like phenotype, where the distance travelled and time spent travelling is markedly higher for the affected mice compared to the controls (35). This hyperactive type behavior has parallels with clinical studies on expremature male children that show an increased incidence of disorders that to some extent involve hyperactivity (7,8).…”
Section: Discussionsupporting
confidence: 70%
“…The deficiencies in the markers of neurodevelopment and neurosteroid-sensitive receptors were associated with increased activity in the open field and environment exploration tests, with the preterm males more active than the control term males. Similar results are seen in mice expressing an attention deficit hyperactivity disorder-like phenotype, where the distance travelled and time spent travelling is markedly higher for the affected mice compared to the controls (35). This hyperactive type behavior has parallels with clinical studies on expremature male children that show an increased incidence of disorders that to some extent involve hyperactivity (7,8).…”
Section: Discussionsupporting
confidence: 70%
“…The discrepancies in these studies regarding the effect of ethanol on MeCP2 expression could be attributed to multiple factors such as the model of study (in vivo animal models or in vitro cultured cells), stage of embryonic development, specific brain region or cell type within a brain region, concentration and duration of ethanol treatment (Bekdash et al, 2013;Chen et al, 2013;Gangisetty et al, 2014;Guo et al, 2012;Kim et al, 2013Kim et al, , 2014Perkins et al, 2013;Subbanna et al, 2014;Tunc-Ozcan et al, 2013). Further supporting the role of MeCP2 in alcoholism, a recent study demonstrated the regulatory effect of MeCP2 on sensitivity to ethanol and drinking ethanol (Repunte-Canonigo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies also implicate the potential of preconception paternal alcohol consumption, which can lead to FASD (Kim et al, 2014;Knezovich and Ramsay, 2012). Previous studies have shown the importance of both alcohol exposure and withdrawal (termination of alcohol consumption) in FASD pathogenesis (Carlson et al, 2012), emphasizing the necessity to study the effect of both ethanol exposure and withdrawal on the central nervous system development (Pierog et al, 1977;Thomas and Riley, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, results of other studies, using male mice exposed to ethanol, implied that an increased methylation of specific DNA loci, e.g. cytosine-rich sequences ("CpG islands") in the promoter region of the DAT gene encoding a dopamine transporter, could be at fault [3]. Disturbed expression of DAT has, indeed, been causally linked to an attentiondeficit/hyperactivity disorder (ADHD)-like behaviour similar to that observed in the offspring of the ethanol-exposed male mice [3]; (cf.…”
Section: Introductionmentioning
confidence: 75%
“…cytosine-rich sequences ("CpG islands") in the promoter region of the DAT gene encoding a dopamine transporter, could be at fault [3]. Disturbed expression of DAT has, indeed, been causally linked to an attentiondeficit/hyperactivity disorder (ADHD)-like behaviour similar to that observed in the offspring of the ethanol-exposed male mice [3]; (cf. review of animal models of ADHD [4] and altered expression of DAT1/SLC6A3 in human ADHD [5]).…”
Section: Introductionmentioning
confidence: 99%